The abduction - Korman, Gordon (New York : Scholastic, 2006)
Aiden works with the FBI in order to rescue his sister Meg, who has been kidnapped.
"An Apple paperback."
730
Accelerated Reader AR
Keywords: Kidnapping -- Juvenile fiction; Brothers and sisters -- Juvenile fiction